Social Impacts of Climate Change in Bolivia : A Municipal Level Analysis of the Effects of Recent Climate Change on Life Expectancy, Consumption, Poverty and Inequality - Andersen, Lykke E.; Verner, Dorte (2012)
This paper analyzes the direct evidence of climate change in Bolivia during the past 60 years, and estimates how these changes have affected life expectancy and consumption levels for each of the 311 municipalities in Bolivia. Contrary to the predictions of most general circulation models, the evidence shows a consistent cooling trend of about 0.2°C per decade over all highland areas, slight and scattered evidence of warming in the lowlands, and no systematic changes in precipitation. The estimations indicate that the 1°C cooling experienced in the already cold highlands over the past five decades likely has reduced consumption possibilities by about 2-3 percent in these areas. Since the much richer population in the lowlands have benefitted slightly from recent climate change, the simulations suggest that recent climate change has contributed to an increase in inequality and poverty in Bolivia. Poor and indigenous peoples in the highlands are among the most severely affected populations. No statistically significant effect on life expectancy was found.